Inbreeding depression in yield-related traits revealed by high-throughput sequencing in hexaploid persimmon breeding populations - Noriyuki Onoue; Atsushi Kono; Akifumi Azuma; Ryusuke Matsuzaki; Atsushi J. Nagano; Akihiko Sato (Euphytica, 2022)

Phylogeography of the East Asian grassland plant, Viola orientalis (Violaceae), inferred from plastid and nuclear restriction site-associated DNA sequencing data - Haruna Sata; Midori Shimizu; Takaya Iwasaki; Hajime Ikeda; Akiko Soejima; Andrey E. Kozhevnikov; Zoya V. Kozhevnikova; Hyoung-Tak Im; Su-Kil Jang; Takayuki Azuma; Atsushi J. Nagano; Noriyuki Fujii (Journal of Plant Research, 2021)

Cell-Permeable Calpain Inhibitor SJA6017 Provides Functional Protection to Spinal Motoneurons Exposed to MPP+ - Supriti Samantaray; Varduhi H. Knaryan; Angelo M. Del Re; John J. Woodward; Donald C. Shields; Mitsuyoshi Azuma; Jun Inoue; Swapan K. Ray; Naren L. Banik (Neurotoxicity Research, 2020)

Population Growth, Urban Expansion, and Private Forestry in Western Oregon - Jeffrey D. Kline; David L. Azuma; Ralph J. Alig (Forest Science, 2004)
Private forestlands in the United States face increasing pressures from growing populations, resulting in greater numbers of people living in closer proximity to forests. What often is called the “wildland/urban interface” is characterized by expansion of residential and other developed land uses onto forested landscapes in a manner that threatens forestlands as productive socioeconomic and ecological resources. Prevailing hypotheses suggest that such forestlands can become less productive, because forest owners reduce investments in forest management. We develop empirical models describing forest stocking, thinning, harvest, and tree planting in western Oregon, as functions of stand and site characteristics, ownership, and building densities. We use the models to examine the potential impacts of population growth and urban expansion, as described by increasing building densities, on the likelihood that forest owners maintain forest stocking, precommercial thin, harvest, and plant trees following harvest. Empirical results support the general conclusion that population growth and urban expansion are correlated with reduced forest management and investment on private forestlands in western Oregon (USA). Results have potential implications for both economic outputs and ecological conditions, as well as for wildfire risks at the wildland/urban interface. FOR. SCI. 50(1):33–43.

The impact of the CYP2D6 and CYP2C19 genotypes on venlafaxine pharmacokinetics in a Japanese population - T. Fukuda; Y. Nishida; Q. Zhou; I. Yamamoto; S. Kondo; J. Azuma (European Journal of Clinical Pharmacology, 2000)

Circadian variation of the urinary 6β-hydroxycortisol to cortisol ratio that would reflect hepatic CYP3A activity - M. Ohno; I. Yamaguchi; T. Ito; K. Saiki; I. Yamamoto; J. Azuma (European Journal of Clinical Pharmacology, 2000)

CYP2C19 genotypes and omeprazole metabolism after single and repeated dosing when combined with clarithromycin - Q. Zhou; I. Yamamoto; T. Fukuda; M. Ohno; A. Sumida; J. Azuma (European Journal of Clinical Pharmacology, 1999)

Interaction of citrus juices with pranidipine, a new 1,4-dihydropyridine calcium antagonist, in healthy subjects - K. Hashimoto; T. Shirafuji; H. Sekino; O. Matsuoka; H. Sekino; O. Onnagawa; T. Okamoto; S. Kudo; J. Azuma (European Journal of Clinical Pharmacology, 1998)

The effect of Y-25510 injection on the serum levels of some cytokines in healthy adult volunteers - J. Azuma; M. Ogura; I. Yamamoto; M. Hisadome; T. Fukuda; Y. Ikeda; H. Mori; T. Oka; S. Asano (European Journal of Clinical Pharmacology, 1998)

Characterization of neutralizing monoclonal antibody escape mutants of Hantaan virus 76118 - M. Kikuchi; K. Yoshimatsu; J. Arikawa; R. Yoshida; Y.-C. Yoo; Y. Isegawa; K. Yamanishi; S. Tono-oka; I. Azuma (Archives of Virology, 1998)

Protective immunity of Hantaan virus nucleocapsid and envelope protein studied using baculovirus-expressed proteins - K. Yoshimatsu; Y-C. Yoo; R. Yoshida; C. Ishihara; I. Azuma; J. Arikawa (Archives of Virology, 1993)